Pengaruh Persepsi Mahasiswa Progam Studi Non Ekonomi Islam Terhadap Minat Menjadi Nasabah Bank Syariah - Saputra, Hendrik; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2019)
This research was conducted to determine the effect of students' perceptions of Islamic non-economic study programs on the interest in becoming customers of Islamic banks (Case study at the Faculty of Economics, Surabaya State University). This research is a quantitative study which aims to determine how much influence the perception of non-economic Islamic students on the interest of becoming customers in Islamic banks from the results of research conducted by using independent variables perceptions of students with bank interest indicators, profit sharing systems, and Islamic bank products through techniques incidental sampling with 100 respondents and the method of distributing questionnaires, it can be concluded that the perception of Islamic non-economic students as a whole has an effect on the interest in being a customer of Islamic banks